Exploring Bank Syariah Indonesia and It’s Customers Perceptions of Cyber Attacks - Siti Aisah; Syarifuddin Syarifuddin; Rahmad Kurniawan (Islamic Economics and Business Faculty of UIN Antasari, 2023)
System maintenance occurred at Bank Syariah Indonesia on May 8, 2023 delaying all activities of Bank Syariah Indonesia branch offices throughout Indonesia, many customers were disappointed with BSI services. Especially mobile banking services and ATM machines that cannot be used for customers to withdraw funds or other transactions. Not only that, employee activities were also delayed due to system maintenance that occurred. This study aims to determine customer perceptions of cyber attacks that occurred at Bank Syariah Indonesia. The research method used is qualitative research using a descriptive approach. Data were collected using field research methods. The results of this study indicate that customer perceptions of cyber attacks, still do not know the information about hacker attacks. Some just know there is a system maintenance disturbance not a hacker attack. However, some customers know about the attack because of the news on social media and newspapers. Many customers also feel anxious and afraid, wondering what is wrong with BSI which has experienced system disruptions for days. This proves that not all customers know about the attack that occurred. The countermeasures taken by Bank Syariah Indonesia are protecting customer data and controlling and preventing operational risks with tighter system supervision, upgrading windows systems, upgrading antivirus systems, conducting limited operations, positive invitations to customers or the public through social media, or direct visits to customers, limited operations and telemarketing.